Conocimiento de la importancia del uso de protección solar en los padres de familia de las niñas de la Escuela Eliseo Álvarez de la ciudad de Loja. - Sotomayor Palacios, Juliana Sthefanía (2016)
The sun emits different types of radiations, among which should be highlighted the ultraviolet and infrared rays, responsible of beneficial and harmful effects on the skin as is the case of skin cancer. The population at present has the perception that a tanned skin is synonymous with healthy skin. For this reason, the present research work was developed with the objective of determining the importance which has the use of sun protection for the parents of the girls of the school Eliseo Álvarez. The research work was descriptive; it was carried out at "Eliseo Álvarez" school in the city of Loja in which participated 74 parents, to whom a survey was conducted with the prior authorization of the director of the establishment, during the month of June of the year 2015, which consisted of 10 questions previously designed for the purpose. The study allowed us to find out that all the parents have a knowledge of sun protection, of which 33.8% was informed through magazines, 35.1% by means of the television followed by a 17.6% through friends and 13.5% through the internet. In addition, the entire population surveyed considers the use of sun protection important, in order to avoid any disease caused by the exposure to the sun's rayssuch as the appearance of skin cancer. Regarding the application of sunscreen in the respondents: 46.6% applies it once a day, 26% applies it twice a day, 9.6% applies it every 3-4 hours and 13% does not apply it at all and choose to protect themselves from the sun's rays by using the cap, the umbrella and the hat, etc. Key words: sunscreen, photoprotection, parents, girls.